What role derivatives? - Newman, P (Oxford Institute for Energy Studies, 2005)
Over the last thirty years, the leading economies have enjoyed tremendous efficiency gains from increased factor productivity within the energy sector. The amount of oil involved in producing one dollar’s worth of GDP has fallen by nearly 50% in Europe and the USA, and by even more in Japan. But the importance of these gains has been completely overshadowed by massive overall growth in aggregate demand for oil: at around 82 mb/d, global consumption today is eight times larger than it was in the early 1950s. Either way, oil still represents something approaching 40% of the world’s supply of energy.